Cerebral Microvascular Endothelial Cell Apoptosis after Ischemia: Role of Enolase-Phosphatase 1 Activation and Aci-Reductone Dioxygenase 1 Translocation - Zhang, Yuan; Wang, Ting; Yang, Ke; Xu, Ji; Ren, Lijie; Li, Weiping; Liu, Wenlan (Frontiers in Molecular Neuroscience, 2016)
Enolase-phosphatase 1 (ENOPH1), a newly discovered enzyme of the methionine salvage pathway, is emerging as an important molecule regulating stress responses. In this study, we investigated the role of ENOPH1 in blood brain barrier (BBB) injury under ischemic conditions. Focal cerebral ischemia induced ENOPH1 mRNA and protein expression in ischemic hemispheric microvessels in rats. Exposure of cultured brain microvascular endothelial cells (bEND3 cells) to oxygen-glucose deprivation (OGD) also induced ENOPH1 upregulation, which was accompanied by increased cell death and apoptosis reflected by increased 3-(4, 5-Dimethylthiazol-2-yl)-2, 5- diphenyltetrazolium bromide formation, lactate dehydrogenase release and TUNEL staining. Knockdown of ENOPH1 expression with siRNA or overexpressing ENOPH1 with CRISPR-activated plasmids attenuated or potentiated OGD-induced endothelial cell death, respectively. Moreover, ENOPH1 knockdown or overexpression resulted in a significant reduction or augmentation of reactive oxygen species (ROS) generation, apoptosis-associated proteins (caspase-3, PARP, Bcl-2 and Bax) and Endoplasmic reticulum (ER) stress proteins (Ire-1, Calnexin, GRP78 and PERK) in OGD-treated endothelial cells. OGD upregulated the expression of ENOPH1’s downstream protein aci-reductone dioxygenase 1 (ADI1) and enhanced its interaction with ENOPH1. Interestingly, knockdown of ENOPH1 had no effect on OGD-induced ADI1 upregulation, while it potentiated OGD-induced ADI1 translocation from the nucleus to the cytoplasm. Lastly, knockdown of ENOPH1 significantly reduced OGD-induced endothelial monolayer permeability increase. In conclusion, our data demonstrate that ENOPH1 activation may contribute to OGD-induced endothelial cell death and BBB disruption through promoting ROS generation and the activation of apoptosis associated proteins, thus representing a new therapeutic target for ischemic stroke.